2011
DOI: 10.1373/clinchem.2010.150375
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia following Treatment for Hyperthyroidism

Abstract: CASEA 17-year-old female was referred to the endocrinology clinic after blood test results suggestive of hyperthyroidism. She had mild symptoms of thyrotoxicosis, including menstrual disturbance with intermittent palpitations and tremor. On examination, the patient was normotensive, tachycardic (100 beats/min), and of slim build with poor dentition. She had a small diffuse goiter without retrosternal extension or bruit. There was conjunctival injection but no evidence of lid lag or proptosis. Auscultation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In addition, in patients with thyroidectomy for Graves' disease, postoperative damages of the parathyroid glands can be also causes of hypocalcemia [1]. However, there have been few reports of symptomatic hypocalcemia after treatment with antithyroid drugs for Graves' disease [2]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in patients with thyroidectomy for Graves' disease, postoperative damages of the parathyroid glands can be also causes of hypocalcemia [1]. However, there have been few reports of symptomatic hypocalcemia after treatment with antithyroid drugs for Graves' disease [2]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there have been few reports of hypocalcemia following treatment for Graves' disease with antithyroid drugs such as methimazole (MMI) [2]. Calcium metabolism is under control through the coordinated actions of parathyroid hormone (PTH) and activated vitamin D, and the most common cause of hypocalcemia in primary care is vitamin D deficiency [3].…”
Section: Introductionmentioning
confidence: 99%
“…There is no consensus about the change in the level of PTH in the blood during thyrotoxicosis. According to the literature data, thyrotoxicosis is accompanied by an increase in PTH concentration, normalising during successful therapy [21]. Although there are opposite works, indicating hypoparathyroidism in Graves' disease [22].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies described an association between 22q11DS and GD [105,106,108,110]. If compared with the general pediatric population, GD in 22q11DS seems to be more frequent and may occur earlier, even under the age of 3 [107].…”
Section: Q112 Deletion Syndromementioning
confidence: 97%
“…Kawame et al reported a case of a 27-month-old 22q11DS female with tachycardia, irritability and seizures due to GD, suggesting that, in addition to the early onset, AITDs in 22q11DS may have an atypical presentation [112]. Additionally, it should be considered that thyrotoxicosis, due to GD, may have a hypercalcemic effect and mask an underling hypoparathyroidism, producing a serum calcium concentration within the normal limits [110].…”
Section: Q112 Deletion Syndromementioning
confidence: 99%